2022
DOI: 10.1155/2022/5067402
|View full text |Cite|
|
Sign up to set email alerts
|

Camrelizumab and Apatinib Combined with Radiotherapy Is Effective in Advanced Oligometastatic Non-Small-Cell Lung Cancer

Abstract: Objective. To investigate the effect of camrelizumab + apatinib combined with radiotherapy on the expression of TRIM27, SCC-Ag, and CYFRA21-1 in advanced oligometastatic non-small-cell lung cancer (NSCLC). Methods. A retrospective analysis of patients with oligometastatic NSCLC who were treated at our hospital from January 1, 2021, to March 31, 2022. Patients who met the inclusion criteria were summarized into an observation group (camrelizumab on the basis of the control group), or a control group (radiothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 25 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…Unfortunately, while DLTs, particularly SRT, are widely used in clinical practice to manage OMD, there is limited evidence to support their use. A review of scientific literature from PubMed in the past year (when a peak of publications is registered) reveals a high number of heterogeneous, retrospective, and small-scale clinical studies conducted in real-world settings [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. While these studies are important, their results cannot formally change the standard of therapy.…”
Section: Definitive Local Therapies In Omdmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, while DLTs, particularly SRT, are widely used in clinical practice to manage OMD, there is limited evidence to support their use. A review of scientific literature from PubMed in the past year (when a peak of publications is registered) reveals a high number of heterogeneous, retrospective, and small-scale clinical studies conducted in real-world settings [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. While these studies are important, their results cannot formally change the standard of therapy.…”
Section: Definitive Local Therapies In Omdmentioning
confidence: 99%
“…While these studies are important, their results cannot formally change the standard of therapy. The evidence ranges from case reports and retrospective series [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ] to phase III randomized trials [ 69 ] such as the SINDAS trial. This trial showed that adding SRT to TKIs significantly improves survival in 133 EGFR-mutated NSCLC OMD patients (median OS TKI plus SRT: 25.5 months vs. 17.4 months in TKI monotherapy).…”
Section: Definitive Local Therapies In Omdmentioning
confidence: 99%
See 1 more Smart Citation
“…This study included subgroup analyses. Among the different therapeutic regimens, RIT plus chemotherapy (RITC) therapy was administered in 2 studies, [13,21] and the pooled ORR and DCR were 50% (95% CI: .079 0.00, .396 [13,18,21] Skin reaction 14 9-19 .00 0.00, .5 [13,14,[16][17][18]20,21] Aspartate aminotransferase increased 18 13-25 .00 0.00, .98 [17][18][19][20] Alanine aminotransferase increased 22 14-31 .00 0.00, .91 [17,18,20] Anemia 20-80%, P = .001) and 69% (95% CI: 39-99%), respectively, while the pooled ORR and DCR were 61% (95% CI: 49-73%, P = .00) and 95% (95% CI: 83-107%) in the RIT therapy group. ORR in the RIT group was pooled using a random-effect model because of slight heterogeneity (I 2 = 47.6%, P = .075) (Figs.…”
Section: Tumor Responsementioning
confidence: 99%
“…After eliminating duplicates (n = 257), titles and abstracts were browsed and filtered. The full text of the remaining 42 studies was screened, and 10 articles [13][14][15][16][17][18][19][20][21][22] were finally included according to the inclusion criteria. The literature review and identification processes are shown in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%